2019
DOI: 10.18295/squmj.2018.18.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Primary Essential Cutis Verticis Gyrata: A scalp condition that may appear in various disorders

Abstract: Interesting Medical Image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Other symptoms include pruritus, generalized headaches, or diffuse hair loss, as seen in this case [8,10]. It has been postulated that primary essential CVG may be hormonally driven, as many of the case reports demonstrate a male post-pubertal presentation; however, no hormonal alteration has successfully been correlated [9,10]. Primary non-essential CVG is typically affiliated with underlying neuropsychiatric disorders, such as seizures, mental retardation, and other brain or ophthalmological conditions [11].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Other symptoms include pruritus, generalized headaches, or diffuse hair loss, as seen in this case [8,10]. It has been postulated that primary essential CVG may be hormonally driven, as many of the case reports demonstrate a male post-pubertal presentation; however, no hormonal alteration has successfully been correlated [9,10]. Primary non-essential CVG is typically affiliated with underlying neuropsychiatric disorders, such as seizures, mental retardation, and other brain or ophthalmological conditions [11].…”
Section: Discussionmentioning
confidence: 86%
“…Many patients are asymptomatic, and they present for evaluation due to cosmetic reasons. Other symptoms include pruritus, generalized headaches, or diffuse hair loss, as seen in this case [8,10]. It has been postulated that primary essential CVG may be hormonally driven, as many of the case reports demonstrate a male post-pubertal presentation; however, no hormonal alteration has successfully been correlated [9,10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Majority of the studies reported insignificant family history of CVG (2,9,11) . We observed that the majority of patient's age of onset of CVG was below 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are reports of CVG associated with acromegaly. [1][2][3][4] On histology, the findings are variable and include a normal skin architecture, zones that present skin hypertrophy, areas of thickened connective tissue with hypertrophy or hyperplasia of adnexal structures, and trapped apocrine and eccrine glands. 2 There are scarce reports on the use of imaging in CVG, including computed tomography (CT) and magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%